NILAl-NILAI RELIGIUS PUISI MENGUTIP MAKNA TAMASYA PURBA KARYA HAFNEY MAULANA - Sum, Tengku Muhammad (Jurnal Ilmu Budaya, 2018)
Apoet, through his orher poem, conveys message which expresses his orher soul. The soul which is led by his or her religious values. One of the poets whose religious values are strong in his poems is Hafney Maulana. A poet from Riau who writes his poems in Malay language. From his poems, we are asked to see his life journey to understand the essence of life as human being who should realize his position in relation to Allah, his creator.